1970
DOI: 10.3758/bf03210206
|View full text |Cite
|
Sign up to set email alerts
|

Form identification in peripheral vision

Abstract: Outlined and solid-sur/aced metric histoforms and polygons we;e employed in an identification task where choice forms were fixed at 0 deg and target forms at six points along the temporal horizontal meridian in the periphery (nasal retina). Accuracy in the identification of solid-surfacedpolygons in the far periphery (80 deg from the fovea) was much higher than has been previously reported. Polygons were identified more quickly than h istaforms, but a significant difference was not obtained between the speed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
13
0

Year Published

1972
1972
1997
1997

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 15 publications
3
13
0
Order By: Relevance
“…Recent evidence (Kawabata, 1982) suggests that fIlling in at the blind spot is contingent upon the visual systern's response to stimulation of an area of the retina directly around the optic disk, falling between 3 0 and 5.2 0 from the center of the blind spot; the functional size of the blind spot is 3 0 in diameter (Menzer & Thurmond, 1970). Filling in is also dependent upon similarity grouping, suggesting that the process of completion occurs with respect to the perceptual segregation of different stimuli (Kawabata, 1984).…”
mentioning
confidence: 99%
“…Recent evidence (Kawabata, 1982) suggests that fIlling in at the blind spot is contingent upon the visual systern's response to stimulation of an area of the retina directly around the optic disk, falling between 3 0 and 5.2 0 from the center of the blind spot; the functional size of the blind spot is 3 0 in diameter (Menzer & Thurmond, 1970). Filling in is also dependent upon similarity grouping, suggesting that the process of completion occurs with respect to the perceptual segregation of different stimuli (Kawabata, 1984).…”
mentioning
confidence: 99%
“…In terms of form perception, Zigler et al, (1930) found a significant drop in form identification between 25' and 30' . Menzer and Thurmond (1970) found that accuracy in the identification of solid-surfaced polygons in the far periphery (80' from the fovea) was much higher than had been previously reported, and hypothesized that spatial summation of rod receptors beyond 20' of angular eccentricity in the nasal retina was directly proportional to the density of rod receptors.…”
Section: Introductionmentioning
confidence: 49%
“…1 the circled dots represent the ones that were omitted in the original experiment-the sides being omitted in certain trials and the corners in others.) Since it is known that, under certain conditions, retinal locus may play an important role in form r e c o g n i tion (Hershenson, 1969;Menzer & Thurmond, 1970), the possibility that retinal locus or some difference in acuity as a function of locus might have substantially biased our data must be considered.…”
mentioning
confidence: 99%